The Moderating Effect of Top Management Team’s Power on the Relationship between CPA Independence & Audit Quality - Ching Yen Li; Chao Sheng Liu; Faradillah Amalia Rivai (International Journal of Research in Vocational Studies (IJRVOCAS), 2022)
This research integrates the top management teams (TMT)power theory, CPA economic independence theory, and reputation maintenance theory to explore the impact on audit quality. This study used the sample of firms listed on the Taiwan Stock Exchange (TSE) and Taipei Exchange (TPEx) from 2009 to 2016. The empirical results show that as the TMT power of Taiwan companies increases, the audit quality is higher. It is different from the general research that the TMT will conduct earning management based on self-interested behavior. The inference is due to Taiwan's relatively high proportion of family companies. In the face of the trend of social responsibility and the requirements of regulatory agencies, the company’s strategy of maintaining corporate image and successfully operating over to the next generation is presented with high audit quality. In addition, when CPAs face important clients, the CPA’s economy depends on important customers is greater than the effect of reputation maintenance, the audit quality will be reduced. When the TMT power is greater, it will offset the CPA's economic independence effect and enhance the audit quality.